Relativistic Impact on Dust-Electron-Acoustic Solitary Waves in An Unmagnetized Plasma with Nonextensive Ions - Rafia Khanam; Satyendra Nath Barman; Muktarul Rahman (East European Journal of Physics)
The nonlinear properties of the dust-electron-acoustic (DEA) solitary waves and their propagating behaviours are theoretically studied in an unmagnetized relativistic plasma model. Such plasma is composed by the weakly relativistic electrons, nonextensive distributed ions and negatively charged immobile dust particles. Staring from a set of unidirectional fluid equations for electrons and nonextensive distribution for ions with Poisson equation, the Korteweg-de Vries (KdV) and modified KdV (mKdV) equations are determined by using the reductive perturbation method technique and their soliton solutions, thus obtained, to analyse the existence regime and basic features of small amplitude DEA solitons. The effects of physical parameters namely ion-to-electron number density ratio (δ), relativistic streaming factor (ν0/c ) and ion nonextensive  parameter (q) on the dynamics of solitary formations are examined in detail. The result shows the existence of both compressive and rarefactive DEA KdV solitons and only compressive DEA mKdV solitons in the range −1 < q < 3, with various δ and ν0/c in the plasma. Additionally, the influences of all the physical parameters on the propagation of DEA solitary waves corresponding to the KdV and mKdV equations are numerically analysed within the paper. The results of this study might help clarify the basic characteristics of nonlinear travelling waves propagating in both laboratory and space plasma as well as astrophysical plasma environments.